The media of Consumption and the Consumption of time: How a consumer in fast-paced economy use traditional and new media tools - Nhedzi,Abyshey (2019)
Research is ongoing about how the New Media impact on Traditional Media. Despite rapid change in the options for how we can interact with and consume media, some of our preferences for needs to consume have not shifted dramatically. This research aims to investigate the patterns of media consumption, and assesses the amount of time people allocate to different media. The study is informed by uses and gratifications theory (UGT), channel complementarity theory and time allocation theory. The article looks at the amount of time spent reading newspapers and magazines, watching television, listening to the radio, using the old or new media, and activities online and offline while at work or out of the work. It investigates whether traditional media are still relevant in this new media environment and identifies consumption practices. A survey was held among consumers who have various media experiences (N = 400) ━ and for the first time in Zimbabwe. Differences between consumers (media users) using traditional media channels and those using new media platforms are identified and discussed. However, some challenges exist, such as the limited number of Apple iPads and tablets. These findings implied that targeting the millennials remains a challenge as respondents are fragmented across various media platforms.